Ang Musika sa Pilipinas: Pagbuo ng Kolonyal na Polisi, 1898-1935 - Navarro, Raul Casantusan (Humanities Diliman: A Philippine Journal of Humanities, 2007)
This paper argues that music, particularly vocal music, was a prime tool in the dissemination of the American colonial worldview. Utilized in public schools, music introduced a culture forged in the context of American life, thus bringing a whole world of beliefs and a process of cultural homogenization that pervaded American colonial schools. Given the structured public educational system the Americans created in the Islands, the colonial project of "a true general Philippine culture" in musical terms have almost resulted in homophony with the Americans whistling away the melody and the Filipinos doing the accompaniment. The author tries to show the Filipino artists' resistance to the hegemonic cultural imposition of the new colonial masters.